Pengaruh Slow Tourism Terhadap Revisit Intention di TWA Gunung Papandayan - Rizky Ahmad Nugraha; Rohimat Nurhasan; Stanny Dhamayanty (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The purpose of this study is to examine how the implementation of the Slow Tourism concept influences tourists’ revisit intention at Taman Wisata Alam Gunung Papandayan. Amid the growing interest in nature-based tourism and meaningful travel experiences, Slow Tourism has become an important approach as it encourages tourists to enjoy their journeys at a relaxed pace, appreciate the environment, and develop a stronger attachment to the destination. This study employs a quantitative approach by conducting a survey of tourists who have previously visited Gunung Papandayan. The findings demonstrate that Slow Tourism has a positive and significant influence on tourists’ intention to revisit. The stronger the calm and authentic travel experiences, along with tourists’ engagement with nature and local culture, the greater the likelihood of tourists returning to the destination. These findings indicate that the Slow Tourism concept functions not only as a travel approach but also as a destination management strategy in building a positive destination image and enhancing tourist loyalty. It is expected that the results of this study can be practically utilized by nature-based destination managers to develop more sustainable and meaningful tourism experiences, as well as serve as an academic reference for future research.